Has India’s Economic Growth Become More Pro-Poor in the Wake of Economic Reforms? - Datt, Gaurav (2012)
The extent to which India's poor have benefited from the country s economic growth has long been debated. This paper revisits the issues using a new series of consumption-based poverty measures spanning 50 years, and including a 15-year period after economic reforms began in earnest in the early 1990s. Growth has tended to reduce poverty, including in the post-reform period. There is no robust evidence that the responsiveness of poverty to growth has increased, or decreased, since the reforms began, although there are signs of rising inequality. The impact of growth is higher for poverty measures that reflect distribution below the poverty line, and it is higher using growth rates calculated from household surveys than national accounts. The urban-rural pattern of growth matters to the pace of poverty reduction. However, in marked contrast to the pre-reform period, the post-reform process of urban economic growth has brought significant gains to the rural poor as well as the urban poor.